Prevalence and risk factors of molar incisor hypomineralization in school children: A cross-sectional study in North Kerala, India - Krishna Kumar Ramakrishnan; Joby Peter; Hridya Menon (Journal of Orofacial Sciences, 2023)
Introduction: Molar incisor hypomineralization (MIH) is a developmental enamel defect affecting permanent molars and incisors, leading to dental challenges. The prevalence and associated risk factors of MIH vary globally, highlighting the need for region-specific studies. The primary objectives of this cross-sectional study were to determine the prevalence of MIH in 7- to 11-year-old school children, investigate associated risk factors, and analyze the clinical manifestations. Materials and methods: A random sample of 10,000 children aged 7 to 11 years from 10 primary schools in North Kerala underwent oral examinations. The study utilized a two-part proforma, including demographic details, parental interviews, and clinical assessments using a modified developmental defect of enamel index. The data were analyzed using the chi-square test and SPSS software. Ethical approval and parental consent were obtained. Results: Out of 2170 children examined, the prevalence of MIH was 8.2%. Males showed a higher prevalence (62.92%), with maxillary molars being predominantly affected. The study revealed significant associations between MIH and antenatal factors, antibiotic usage, and maternal illnesses. Maxillary molars were more frequently affected than mandibular molars, with specific teeth showing varying degrees of susceptibility. Conclusion: As children’s age increased, the severity of MIH defects in the first permanent molars escalated, indicating progressive enamel defects. The prevalence of MIH was more pronounced in the upper arch, with both maxillary and mandibular first permanent molars being equally affected. The study identified factors such as polychlorinated biphenyls (PCBs)/dioxins, medical illness problems, malnutrition, fluoride exposure, common medical diseases, and genetic disorders as potential contributors to MIH defects. Early diagnosis and intervention are crucial for managing the challenges posed by MIH-affected teeth.